Identification of a 2-phenoxychromone derivative as a novel inhibitor of lipid droplet formation in hepatocytes and adipocytes - Yu-Tsen Hsieh; Tung-Hsuan Kang; Hsin-Yi Hung; Yi-Han Chang; Kuan-Chen Cheng; Chia-Yih Wang; Wen-Tai Chiu; Pai-Sheng Chen; Shih-Chieh Lin; I-Chen Peng (Results in Chemistry)
Dysregulated lipid droplet (LD) accumulation in hepatocytes increases the risk of metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as non-alcoholic fatty liver disease (NAFLD), the most common chronic liver disease worldwide. Furthermore, excessive accumulation of LD in adipocytes leads to obesity, insulin resistance, and metabolic complications, including MASLD. Therefore, there is a need to develop pharmacological inhibitors for reducing LD accumulation in hepatocytes and adipocytes. In this study, we used HepG2 and 3T3-L1 cells to investigate the LD-inhibiting effects of a 2-phenoxychromone derivative, 7-methoxy-2-(3′,4′,5′-trimethoxyphenoxy)-chromen-4-one (compound N4). Compound N4 repressed LD accumulation induced by oleic acid (OA) and linoleic acid (LA) in HepG2 cells with IC50 values of 44.5 ± 7.1 μM and 52 ± 11.8 μM, respectively. Compound N4 showed no significant cell cytotoxicity with a CC50 value of 293.7 ± 12.9 μM in HepG2 cells. Mechanistically, compound N4 inhibited LD formation induced by OA through reducing acetyl-CoA carboxylase 1 (ACC1), sterol regulatory element-binding protein 1 (SREBP1), cluster of differentiation 36 (CD36), and diacylglycerol O-acyltransferase 2 (DGAT2) mRNA expression. Moreover, compound N4 inhibited LD accumulation induced by LA through reducing CD36 and DGAT2 mRNA expression. Compound N4 also decreased LD formation and adipogenesis with an IC50 value of 35.9 ± 6.5 μM in 3T3-L1 cells. Compound N4 displayed no significant cell cytotoxicity with a CC50 value of 42.6 ± 3.2 μM, and it inhibited LD accumulation through reducing ACC1, SREBP1, CD36, DGAT2, CCAAT/enhancer binding protein α/β, and peroxisome proliferator-activated receptor γ mRNA expression in 3T3-L1 cells. Based on these findings, we identify compound N4 as a novel LD inhibitor in hepatocytes and adipocytes, which can be developed further for managing MASLD and obesity.